MiR-204 silencing in intraepithelial to invasive cutaneous squamous cell carcinoma progression. Issue 1 (December 2016) - Toll, Agustí; Salgado, Rocío; Espinet, Blanca; Díaz-Lagares, Angel; Hernández-Ruiz, Eugenia; Andrades, Evelyn; Sandoval, Juan; Esteller, Manel; Pujol, Ramón; Hernández-Muñoz, Inmaculada
Abstract Background Cutaneous squamous cell carcinoma (cSCC) is the second most common skin cancer and frequently progresses from an actinic keratosis (AK), a sun-induced keratinocyte intraepithelial neoplasia (KIN). Epigenetic mechanisms involved in the phenomenon of progression from AK to cSCC remain to be elicited. Methods Expression of microRNAs in sun-exposed skin, AK and cSCC was analysed by Agilent microarrays. DNA methylation of miR-204 promoter was determined by bisulphite treatment and pyrosequencing. Identification of miR-204 targets and pathways was accomplished in HaCat cells. Immunofluorescence and immunohistochemistry were used to analyze STAT3 activation and PTPN11 expression in human biopsies. Results cSCCs display a marked downregulation of miR-204 expression when compared to AK. DNA methylation of miR-204 promoter was identified as one of the repressive mechanisms that accounts for miR-204 silencing in cSCC. In HaCaT cells miR-204 inhibits STAT3 and favours the MAPK signaling pathway, likely acting through PTPN11, a nuclear tyrosine phosphatase that is a direct miR-204 target. In non-peritumoral AK lesions, activated STAT3, as detected by pY705-STAT3 immunofluorescence, is retained in the membrane and cytoplasm compartments, whereas AK lesions adjacent to cSCCs display activated STAT3 in the nuclei. Conclusions Our data suggest that miR-204 may act as a "rheostat" that controls the signalling towards the MAPK pathway or the STAT3 pathway in the progression from AK to cSCC.